Transcriptome Analysis Identifies Piwi-Interacting RNAs as Prognostic Markers for Recurrence of Prostate Cancer - Zuo, Yuanli; Liang, Yu; Zhang, Jiting; Hao, Yingyi; Li, Menglong; Wen, Zhining; Zhao, Yun (Frontiers in Genetics, 2019)
Prostate cancer remains the second leading cause of male cancer death, and there is an unmet need for biomarkers to identify patients with such aggressive disease. Piwi-inteacting RNAs (piRNAs) have been classified as transcriptional and posttranscriptional regulators in somatic cells. In this study, we discovered three piRNAs as novel prognostic markers and their association with prostate cancer biochemical recurrence was confirmed in validation data set. To obtain a better understanding of piRNA expression patterns in prostate cancer and to find gene coexpression with piRNAs, we performed weighted gene coexpression network analysis. Target genes of three piRNAs have also been predicted based on base complementarity and expression correlativity. Functional analysis revealed the relationships between target genes and prostate cancer. Our work also identified differential expression of piRNAs between Gleason stage 3 + 4 and 4 + 3 prostate cancer. Overall, this study may explain the roles and demonstrate the potential clinical utility of piRNAs in prostate cancer in a way.